The rhetoric of the real: stereotypes of rural youth in American reality television and stock photography. Issue 3 (4th May 2017) - Massey, Carissa
ABSTRACT: Through an examination of the visual rhetoric of identity presented by reality shows, especially Here Comes Honey Boo Boo, this paper explores ways in which American reality television and related media images construct, deploy, and reiterate visual stereotypes about whites from rural regions of the United States. Its focus is the relationship between image rhetoric and social identity expression and how they converge to create a discourse loop. Combining identity theory and visual rhetoric studies as a unique methodological lens, this paper focuses on why and how stereotypes circulate in the so-called realistic media. The implications of broadening stereotype study to include all varieties of visual artifacts in analysis of specific tropes are particularly important to the study of stereotypes of white rural others, especially since such imagery has increased in volume in recent years and appears in several different types of media.